2018
DOI: 10.1111/jgs.15294
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and Phonemic Verbal Fluency Discrepancy in Mild Cognitive Impairment: Potential Predictor of Progression to Alzheimer's Disease

Abstract: Mean discrepancy score for those who progressed to AD (2.7) was significantly lower than for those who retained a MCI diagnosis (4.8) and normal controls (7.7) (p<.001). Logistic regression revealed that, for each unit decrease in discrepancy score at baseline, the odds of progressing to AD were 9% greater. (Exp(B) = 1.09, p=.02) CONCLUSION: Individuals with MCI have less of a semantic advantage than those without MCI. Those with MCI presenting with a phonemic advantage at initial assessment warrant close foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…We did not observe significant interactions between Group × Evaluation time in any of the measures; longitudinal patterns of increase, decline or stability were therefore similar in all groups, independently of the stage of cognitive impairment. Direct comparison of these findings is not possible, due to the lack of longitudinal research on ToT; however, our findings on semantic fluency are consistent with those reported by Vaughan et al (2018), who did not find significant differences in semantic fluency (animals) between MCI patients who progressed to AD and MCI non-progressors in a follow-up study with a mean duration of 2.46 years. Pakhomov et al (2016) also did not find any differences in semantic fluency between MCI and AD participants in a longer longitudinal design, although differences between the cognitively unimpaired group and both MCI and AD groups were reported.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We did not observe significant interactions between Group × Evaluation time in any of the measures; longitudinal patterns of increase, decline or stability were therefore similar in all groups, independently of the stage of cognitive impairment. Direct comparison of these findings is not possible, due to the lack of longitudinal research on ToT; however, our findings on semantic fluency are consistent with those reported by Vaughan et al (2018), who did not find significant differences in semantic fluency (animals) between MCI patients who progressed to AD and MCI non-progressors in a follow-up study with a mean duration of 2.46 years. Pakhomov et al (2016) also did not find any differences in semantic fluency between MCI and AD participants in a longer longitudinal design, although differences between the cognitively unimpaired group and both MCI and AD groups were reported.…”
Section: Discussionsupporting
confidence: 85%
“…Semantic fluency was also significantly more impaired in the MCI worsened patients than in the other two groups. As performance in fluency tasks rely on the successful semantic and phonological processes, this finding further confirms that semantic access is not as good as phonological access in differentiating the stages in the continuum between unimpaired cognition and dementia (Juncos-Rabadán et al, 2013;Vaughan et al, 2018). In addition, semantic fluency remained stable during the evaluation times, and even increased slightly (although not statistically significantly), suggesting that it is not a good predictor of worsening cognitive status.…”
Section: Discussionmentioning
confidence: 54%
“…However, as recognized by Lamar et al (2013) and as demonstrated by the recent findings of Vaughan et al (2016Vaughan et al ( , 2018, inclusion in a test protocol of a semantic fluency task that can then function as a contrast with phonemic fluency has real potential to add value to the screening for MCI and dementia. Previously, Carew et al (1997) had found that the capacity to use semantic organizational strategies was relatively intact in patients with ischemic vascular dementia (VD) compared to patients with AD.…”
Section: Verbal Fluency Tasksmentioning
confidence: 99%
“…Although they noted no significant differences between VD and AD participants in terms of overall number of words generated on the "animals" semantic fluency task, they concluded that the performance of VD participants was consistent with search-retrieval deficits, while for AD participants degraded semantic knowledge likely underpinned poor performance (Carew et al, 1997). Thus, consideration of both phonemic and semantic fluency, and the discrepancy scores between these tasks can assist differentiating between normal and pathological subtypes of cognitive aging (Lamar et al, 2013;Vaughan et al, 2018).…”
Section: Verbal Fluency Tasksmentioning
confidence: 99%
“…A standardised set up was used for the TUG and TUGdt tests, including video documentation. The TUGdt consisted of TUG combined with the verbal attention-demanding task of naming different animals, which challenges semantic memory and executive function [38,39]. The task of naming animals is based on a well-established verbal fluency test [40], which is commonly used for assessing semantic memory and has been used as a component in various dual-task tests [24,41].…”
Section: Timed Up-and-go and Timed Up-and-go Dual-task Testsmentioning
confidence: 99%